Reconstructing Village Druwe Land Administration to Protect the Communal Land in Bali - Sukirno Sukirno; Muh Afif Mahfud; Muhammad Fahad Malik (Administrative Law Departement Faculty of Law Universitas Sebelas Mare, 2024)
The phenomenon of individualization of customary land, which is communal land, occurs in many customary law communities in Bali, such as those in Bangli and Lembang. The reason for this phenomenon is that the land administration in Bali's customary law communities only includes the names of the people who control the customary land. This makes it difficult for indigenous villages in Bali to prove their rights to the land. This research aims to analyze the weaknesses in the administration of customary land in customary law communities in Bali and also to construct an ideal customary land administration to protect the communal rights of customary law communities over their land. This research is a non-doctrinal (socio-legal) research that examines the administration of customary land in reality and the understanding of indigenous peoples regarding this matter. This research is a prescriptive research that uses primary data obtained through in-depth interviews and analyzed qualitatively. This research identifies three primary weaknesses in the administration of customary land in Bali, namely weak legal pluralism, insufficiently participatory land policies, and the existence of land administration that is not detailed. Therefore, the ideal construction of customary land administration in Bali is a change in legal politics to strong legal pluralism including changes in the conversion provisions of the Basic Agrarian Law which convert customary land to property rights, participatory land administration even up to the stage of citizen control and also detailed land administration including land history, land mutation, land boundaries and land stewardship.